Analysis of two novel midgut-specific promoters driving transgene expression in Anopheles stephensi mosquitoes. - Tony Nolan; Elisa Petris; Hans-Michael Müller; Ann Cronin; Flaminia Catteruccia; Andrea Crisanti (PLoS ONE, 2011)
BACKGROUND:Tissue-specific promoters controlling the expression of transgenes in Anopheles mosquitoes represent a valuable tool both for studying the interaction between these malaria vectors and the Plasmodium parasites they transmit and for novel malaria control strategies based on developing Plasmodium-refractory mosquitoes by expressing anti-parasitic genes. With this aim we have studied the promoter regions of two genes from the most important malaria vector, Anopheles gambiae, whose expression is strongly induced upon blood feeding. RESULTS:We analysed the A. gambiae Antryp1 and G12 genes, which we have shown to be midgut-specific and maximally expressed at 24 hours post-bloodmeal (PBM). Antryp1, required for bloodmeal digestion, encodes one member of a family of 7 trypsin genes. The G12 gene, of unknown function, was previously identified in our laboratory in a screen for genes induced in response to a bloodmeal. We fused 1.1 kb of the upstream regions containing the putative promoter of these genes to reporter genes and transformed these into the Indian malaria vector A. stephensi to see if we could recapitulate the expression pattern of the endogenous genes. Both the Antryp1 and G12 upstream regions were able to drive female-predominant, midgut-specific expression in transgenic mosquitoes. Expression of the Antryp1-driven reporter in transgenic A. stephensi lines was low, undetectable by northern blot analysis, and failed to fully match the induction kinetics of the endogenous Antryp1 gene in A. gambiae. This incomplete conservation of expression suggests either subtle differences in the transcriptional machinery between A. stephensi and A. gambiae or that the upstream region chosen lacked all the control elements. In contrast, the G12 upstream region was able to faithfully reproduce the expression profile of the endogenous A. gambiae gene, showing female midgut specificity in the adult mosquito and massive induction PBM, peaking at 24 hours. CONCLUSIONS:Our studies on two putative blood-meal induced, midgut-specific promoters validate the use of G12 upstream regulatory regions to drive targeted transgene expression coinciding spatially and temporally with pre-sporogonic stages of Plasmodium parasites in the mosquito, offering the possibility of manipulating vector competence or performing functional studies on vector-parasite interactions.